Chlorpyrifos Bioassay and Resistance Monitoring of San Joaquin Valley California Citricola Scale Populations - Ouyang, Yuling; Chueca, Patricia; Scott, Sara J.; Montez, Greg H.; Grafton-Cardwell, Elizabeth E. (2017)
The responses to chlorpyrifos of six populations of citricola scale, Coccus pseudomagnoliarum (Kuwana) (Hemiptera: Coccidae), were tested using a leaf dip bioassay, and two- to nine-fold resistances were found. LC50 responses of nymphs ranged from 7.5 to 68.9 ppm and LC90 responses ranged from 20 to 222 ppm chlorpyrifos. A population tested monthly during August–October showed up to 3.5-fold differences in LC50 responses but no differences in LC90 responses as scale size increased. A diagnostic concentration of 178 ppm chlorpyrifos was used to test 93 populations from throughout the San Joaquin Valley California during 2006–2009 by using a leaf dip bioassay. Of the populations tested, 41% showed >20% survival after exposure to the diagnostic concentration of chlorpyrifos, indicating resistance problems. Research is needed to relate the level of survival of the scales in the bioassay to the field efficacy of the insecticide. Tulare County citrus growers applied a higher number of organophosphate and carbamate insecticides during the 15-yr period from 1994 to 2008, and these orchards showed a higher average scale survival of chlorpyrifos and a higher number of locations with resistant scale compared with the other San Joaquin Valley counties. Chlorpyrifos resistance is a significant issue for citricola scale management because biological control is ineffective in the San Joaquin Valley and the alternative neonicotinoid and insect growth regulator (IGR) insecticides require more frequent application.